Analisis Kebutuhan Informasi Pengguna di Perpustakaan UISU - Rizki Febri Yanti;; Audina Putri; Dea Amanda; Franindya Purwaningtyas (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
This study aims to identify the information needs of users in the UISU library. This research is located at the Islamic University of North Sumatra (UISU) which is located on Jalan Sisingamangaraja, Teladan Barat, Medan Kota District, Medan City, North Sumatra. The method to be used in this research is a qualitative research method which is described descriptively. The technique used in collecting qualitative data is using direct observation techniques. The results of this study concluded that the collections contained in the Library of the Islamic University of North Sumatra (UISU) were insufficient, but each faculty had its own library. Keywords: Information needs, library users, college library.